2021
DOI: 10.1111/tri.13876
|View full text |Cite
|
Sign up to set email alerts
|

Pancreas utilization rates in the UK – an 11‐year analysis

Abstract: Utilization of pancreases for transplantation remains inferior to that of other organs. Herein, we analysed UK pancreas discards to identify the reasons for the low utilization rates. Data on all pancreases offered first for solid organ transplantation between 1st January 2005 and 31st December 2015 were extracted from the UK Transplant Registry. The number of organs discarded, reasons and the time point of discard were analysed. A centre specific comparison was also undertaken. 7367 pancreases were offered fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…A quarter of patients may remain insulin independent, with HbA1c concentrations of less than or equal to 6.5%, for at least 10 years, with either islet transplantation alone or isletafter-kidney transplantation [55]. Moreover, the glucose control associated with excellent islet graft function closely matches glucose values measured in healthy adults: median glucose 103 mg/dL (95)(96)(97)(98)(99)(100)(101)(102)(103)(104)(105)(106)(107)(108)(109)(110)(111)(112), glucose standard deviation around the mean value 14 (11-20), 0% time >180 mg/dL, 0% time <54 mg/dL, HbA1c 5.6 (5-5.8) [56]. Additionally, a significant improvement of quality of life after islet transplant has been documented by using standardized psychometric instruments and interviews carried on by psychologists [47,[57][58][59][60][61][62][63][64].…”
Section: Islet Transplantation Todaymentioning
confidence: 71%
See 1 more Smart Citation
“…A quarter of patients may remain insulin independent, with HbA1c concentrations of less than or equal to 6.5%, for at least 10 years, with either islet transplantation alone or isletafter-kidney transplantation [55]. Moreover, the glucose control associated with excellent islet graft function closely matches glucose values measured in healthy adults: median glucose 103 mg/dL (95)(96)(97)(98)(99)(100)(101)(102)(103)(104)(105)(106)(107)(108)(109)(110)(111)(112), glucose standard deviation around the mean value 14 (11-20), 0% time >180 mg/dL, 0% time <54 mg/dL, HbA1c 5.6 (5-5.8) [56]. Additionally, a significant improvement of quality of life after islet transplant has been documented by using standardized psychometric instruments and interviews carried on by psychologists [47,[57][58][59][60][61][62][63][64].…”
Section: Islet Transplantation Todaymentioning
confidence: 71%
“…1). Efforts are ongoing to push to a broader dimension islet transplantation [54], including (i) implementation of scheme for donor and recipient selection and organ allocation to increase pancreas utilization [94][95][96]; (ii) improvement and standardization of islet isolation process and its best codification by regulatory bodies [97][98][99][100]; (iii) monitoring of transplanted islets by noninvasive imaging techniques [101,102]; (iv) development of biomarkers to assess the efficacy of the immunosuppression/immunomodulation strategies [92,[103][104][105][106][107]; (v) identification of alternative transplantation sites [108]; (vi) creation of an ideal bio-artificial niche for islet survival by bioengineering approaches [109,110]; and (vii) use of immune-isolation techniques, such as hydrogel polymers that shield pancreatic islet from immune cell attack [111,112]. On the other hand, there is increasing enthusiasm for the use of unlimited alternative sources of transplantable insulin-producing cells.…”
Section: New Horizon For the Treatment Of Diabetes With Cell Therapiesmentioning
confidence: 99%
“…There are ominous trends signaling that pancreas transplantation activity has flat-lined globally (Angelika Gruessner, personal communication, January 2023). 4,[17][18][19][20][21][22] The annual number of non-US cases surpassed cases in the United States in 2008 and has continued over time. 4 The number of pancreas transplants performed globally peaked at about 2600 in 2011, declined to 2000 in 2020 during the COVID-19 pandemic, and slowly recovered to about 2100 in 2021.…”
Section: Pancreas Transplant Activity Worldwidementioning
confidence: 99%
“…18 In the United Kingdom, from 2009 to 2016, the pancreas nonrecovery rate was 49.7%, and the discard rate following pancreas recovery was 38%. 19 The number of pancreas transplants performed in the United Kingdom decreased from 214 in 2013/2014 to 131 in 2021/2022. 20 In the Australia/New Zealand registry, only 36 SPKTs and 1 PAK transplant were performed in 2021, which was down from 52 pancreas transplants performed in 2016.…”
Section: Pancreas Transplant Activity Worldwidementioning
confidence: 99%
“…2 The causes for this could be multifactorial, mostly attributed to organ-related factors, including cold ischemia time (CIT), graft steatosis, donor age, and mode of death (cardiac versus brain death), rather than the availability of organs. 3 Factors such as organ recovery, packaging, transportation from the retrieval center to the recipient hospital (across cities or provinces), back-table preparation, and recipient characteristics might all contribute to increasing the cold preservation time of the graft. 4,5 Studies have shown prolonged CS of the pancreas graft (>12 h) to be associated with graft failure, thereby leading to the inclusion of this factor in the calculation of the pancreas donor risk index.…”
mentioning
confidence: 99%